Respuesta :

●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●

Hi my lil bunny!

❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙

Let's solve your equation step-by-step.

[tex]2x-3x+5=18[/tex]

Step 1: Simplify both sides of the equation.

[tex]2x-3x+5=18\\2x + -3x + 5 = 18[/tex]

[tex]( 2x + -3x ) + ( 5) = 18[/tex] (Combine Like Terms)

[tex]-x + 5 = 18\\-x + 5 = 18[/tex]

Step 2: Subtract 5 from both sides.

[tex]-x + 5 - 5 = 18 - 5 \\-x = 13[/tex]

Step 3: Divide both sides by -1.

[tex]\frac{-x}{-1} = \frac{13}{-1} \\x = -13[/tex]

Answer : [tex]\boxed {x = -13}[/tex]

❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙

●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●

Have a great day/night!

❀*May*❀

Answer:

[tex] \boxed{ \bold{ \mathsf{ \purple{x = - 13}}}}[/tex]

Step-by-step explanation:

[tex] \mathsf{2x - 3x + 5 = 18}[/tex]

Collect like terms

[tex] \mathsf{ - x + 5 = 18}[/tex]

Move constant to R.H.S and change it's sign

[tex] \mathsf{ - x = 18 - 5} [/tex]

Calculate the difference

[tex] - x = 13[/tex]

Change the signs on both sides of the equation

[tex] \mathsf{x = - 13}[/tex]

---------------------------------------------------------------

[tex] \blue{ \mathsf{verification}}[/tex]

[tex] \mathsf{LHS \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: RHS}[/tex]

[tex] \mathsf{2x - 3x + 5 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: 18}[/tex]

[tex] \mathsf{ = 2 \times ( - 13) - 3 \times ( - 13) + 5}[/tex]

[tex] \mathsf{ - 26 + 39 + 5}[/tex]

[tex] \mathsf{ = 13 + 5}[/tex]

[tex] = 18[/tex]

Thus, LHS = RHS

hope I helped!

Best regards!